ANALYSIS OF AMENDMENTS AND RECOMMENDATIONS OF THE REVISION OF LEGAL ASSISTANCE LAW - Nevey Varida Ariani (NOMOI Law Review, 2021)
The Legal Aid Law was drafted as the legal framework for legal aid for the poor in Indonesia. The provisions of this statutory law have been in place for almost a decade. Even so, there are indications that the implementation of legal aid has not been effective in the field, both as legal aid recipients, legal aid providers, and legal aid administrators. The research problem is how the urgency of changing the Law on Legal Aid for Justice and Equality. Qualitative research methods with a normative juridical approach. The extension of legal protection includes vulnerable and marginalized groups, both witnesses and victims. Harmonization of laws and regulations so as not to cause overlaps in the implementation of legal aid, for example in the position and authority of a legal assistant. The verification period encourages the establishment of a new OBH in the regions. Assistance mechanisms in the form of litigation and non-litigation are not only for the perpetrators but also for the victims, both pre, process and post trial. Government support financing with a special budgeting so that it is transparent and accountable.Keywords: Urgency, Legal Aid, Justice, Equality.